Mass spectrometry-based draft of the mouse proteome - Giansanti, Piero; Samaras, Patroklos; Bian, Yangyang; Meng, Chen; Coluccio, Andrea; Frejno, Martin; Jakubowsky, Hannah; Dobiasch, Sophie; Hazarika, Rashmi R.; Rechenberger, Julia; Calzada-Wack, Julia; Krumm, Johannes; et al. (Nature methods, 2022)
The laboratory mouse ranks among the most important experimental systems for biomedical research and molecular reference maps of such models are essential informational tools. Here, we present a quantitative draft of the mouse proteome and phosphoproteome constructed from 41 healthy tissues and several lines of analyses exemplify which insights can be gleaned from the data. For instance, tissue- and cell-type resolved profiles provide protein evidence for the expression of 17,000 genes, thousands of isoforms and 50,000 phosphorylation sites in vivo. Proteogenomic comparison of mouse, human and Arabidopsis reveal common and distinct mechanisms of gene expression regulation and, despite many similarities, numerous differentially abundant orthologs that likely serve species-specific functions. We leverage the mouse proteome by integrating phenotypic drug (n > 400) and radiation response data with the proteomes of 66 pancreatic ductal adenocarcinoma (PDAC) cell lines to reveal molecular markers for sensitivity and resistance. This unique atlas complements other molecular resources for the mouse and can be explored online via ProteomicsDB and PACiFIC.
CRIS-Team Scopus Importer:2023-03-08